2022
DOI: 10.1093/aob/mcac094
|View full text |Cite
|
Sign up to set email alerts
|

Extreme undersaturation in the intercellular airspace of leaves: a failure of Gaastra or Ohm?

Abstract: Background Recent reports of extreme levels of undersaturation in the internal leaf air spaces have called into question one of the foundational assumptions of leaf gas exchange analysis, that leaf air spaces are effectively saturated with water vapor at leaf surface temperature. Historically, inferring the biophysical states controlling assimilation and transpiration from the fluxes directly measured by gas exchange systems has presented a number of challenges, including: 1) a mismatch in sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 58 publications
0
15
0
Order By: Relevance
“…Conversely, if airspace unsaturation or guard cell water relations is of particular interest, then we would like to know the conductance all the way to airspace and the guard cells. Technological advances enabling quantification of Ψ in vivo at leaf level, using intercellular gel sensors (Jain et al ., 2021; Rockwell et al ., 2022), or at the cellular level, using intracellular protein biosensors (Cuevas‐Velazquez et al ., 2021) may soon enable estimation of K ox dynamics according to both definitions.…”
Section: Benefits Of a Dynamic Koxmentioning
confidence: 99%
“…Conversely, if airspace unsaturation or guard cell water relations is of particular interest, then we would like to know the conductance all the way to airspace and the guard cells. Technological advances enabling quantification of Ψ in vivo at leaf level, using intercellular gel sensors (Jain et al ., 2021; Rockwell et al ., 2022), or at the cellular level, using intracellular protein biosensors (Cuevas‐Velazquez et al ., 2021) may soon enable estimation of K ox dynamics according to both definitions.…”
Section: Benefits Of a Dynamic Koxmentioning
confidence: 99%
“…As with all methods of measuring K leaf or K s‐l (which encompasses K leaf ), our approach assumes a consistent gradient in Ψ across the mesophyll. Some authors have suggested that under extreme conditions, the Ψ gradient within the leaf may become very steep near the end of the flow path for liquid water (Cernusak et al ., 2018; Rockwell et al ., 2022; Wong et al ., 2022), and this would be partially hidden if only a small proportion of mesophyll cells were affected. The conditions used here did not include the extreme transpiration rates where unsaturated mesophyll humidity has been reported, but this might be an interesting focus for future work.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been shown that under high ASD, patchiness (Mott & Buckley, 2000), or unsaturation may occur (Cernusak et al ., 2018), and the mixture of adaxial and abaxial fluxes might mask the occurrence of both. The failure of one or both of these assumptions compromizes the validity of the results, making their identification crucial (Rockwell et al ., 2022). The measurements presented in Fig.…”
Section: Discussionmentioning
confidence: 99%